E-Scrapbook: The Needs of HOTS Oriented Digital Learning Media in Elementary Schools - Antara, I Gede Wahyu Suwela; Dewantara, Kadek Andre Karisma (Universitas Pendidikan Ganesha, 2022)
The adaptation of new habits after the COVID-19 pandemic has an impact on the lack of availability of learning media that can be used to support the learning process. The role of learning media is very important in the learning process, one of which is to facilitate students in practicing higher-order thinking skills as one of the 21st century skills that must be possessed by students. This study aims to analyze the needs and explore the role of teachers in the process of developing digital learning media containing HOTS-based questions in elementary schools. This research is a descriptive research by conducting a needs analysis. The data was collected using observation and interview methods with instruments in the form of observation sheets and interview sheets. Data analysis was carried out qualitatively. The results show that digital-based learning media containing HOTS questions used in post-covid-19 learning are still limited and not varied. In addition, teachers also have not played a major role in developing digital-based learning media containing HOTS questions. This indicates that the development of digital-based learning media containing HOTS questions needs to be developed as an effort to improve the quality of learning after the COVID-19 pandemic.